Genome-Wide Analysis of MicroRNAs in Relation to Pupariation in Oriental Fruit Fly - Zhang, Qiang; Dou, Wei; Pan, Deng; Chen, Er-Hu; Niu, Jin-Zhi; Smagghe, Guy; Wang, Jin-Jun (Frontiers in Physiology, 2019)
Insect metamorphosis is a complex process involving drastic morphological and physiological changes. microRNAs (miRNAs) are a class of endogenous small non-coding RNAs that play key roles in regulating various biological processes, including metamorphosis, by post-transcriptional repression of mRNAs. The oriental fruit fly, Bactrocera dorsalis, is one of the most destructive insect pests in many Asian countries and the Pacific Islands. The regulatory role of miRNAs in B. dorsalis metamorphosis is unclear. To better understand the molecular regulatory mechanisms of miRNAs in pupariation, Illumina sequencing of the wandering stage, the late wandering stage and the white puparium stage of B. dorsalis were performed. Two hundred forty-nine miRNAs, including 184 known miRNAs and 65 novel miRNAs, were obtained. Among these miRNAs, 19 miRNAs were differentially expressed in pupariation, and eight miRNAs showed relative high expression levels (>50 TPM), of which five differentially expressed miRNAs (DEMs) had target differentially expressed genes (DEGs) predicted by the expected miRNA-mRNA negative regulation pattern using the Illumina HiSeq data. Four sets of DEMs and their predicted target DEGs were confirmed by qPCR. Of the four miRNAs, two miRNAs were down-regulated: miR-981, which may target pdpc, and Bdo-novel-mir-55, which potentially regulates spsX1, psB/C and chit3. The other two miRNAs were up-regulated: let-7a-3p, which possibly controls lap, and Bdo-novel-mir-24, which may regulate ipc and sp1/2. This study provides a useful resource to elucidate the regulatory role of miRNAs and understand the molecular mechanisms of metamorphosis.